Внешнее магнитное поле городских трансформаторных подстанций и методы его нормализации - Розов, Владимир Юрьевич; Пелевин, Дмитрий Евгеньевич; Пелевина, Екатерина Дмитриевна (НТУ "ХПИ", 2017)
Целью работы является исследование внешнего магнитного поля городских трансформаторных подстанций (ТП) и методов его уменьшения в близлежащих жилых помещениях до нормативного уровня. Выполнены комплексные экспериментальные исследования магнитного поля частотой 50 Гц, создаваемого типовыми городскими ТП во внешней среде. Показано, что индукция магнитного поля в близлежащих жилых помещениях не превышает нормативного уровня (0,5 мкТл), если помещения расположены на расстояниях более 8 м от корпуса ТП. Предложена мультидипольная математическая модель для расчета внешнего магнитного поля ТП и приведен пример ее практического использования для расчета индукции внешнего магнитного поля, создаваемого в близлежащем жилом помещении ТП мощностью 715 кВА, встроенной в жилой дом. Приведено сравнение результатов расчета и эксперимента. Показано, что встроенные в жилые дома ТП могут создавать в соседних жилых помещениях опасное для здоровья населения магнитное поле с индукцией 1,5-7 мкТл, что в 3-14 раз превышает его нормативный уровень. Предложены методы нормализации внешнего магнитного поля встроенных ТП, основанные на совершенствовании конструкции ТП, а также методах внешнего пассивного и активного экранирования (компенсации).

Research of external magnetic field of urban transformer substations and the methods it reduction to the standard level in the living quarters of nearby. Experiment based on the actual values the measuring magnetic flux density of the alternating magnetic field. Theories of electromagnetic field on quasistatic formulation is basis of external magnetic field of urban transformer substations description. We have made comprehensive experimental researches the magnetic field of a 50 Hz through model urban transformer substations on the external environment. For calculating the external magnetic field of transformer substations the mathematical model of multidipole is proposed. It practical uses for induction external magnetic field of calculating created in nearby built in house transformer substations power 715 kVA is proposed. Comparison of results calculation and experiment was conducted. We have established that magnetic flux density of the magnetic field does not exceed standard level in the living quarters of nearby (0.5 µT) if quarters the location distances of more than 8 m from the transformer substation on the first time. Transformer substations in the builtin houses can create the dangerous to public health magnetic field which induction 1.5-7 µT in neighboring living quarters. It exceeds the normative level in 3-14 times. We have proposed normalization methods of the external magnetic field builtin transformer substations. Methods are based on improving construction transformer substations. And methods of external passive and active shielding are considered.
External magnetic field of urban transformer substations and methods of its normalization
Keywords: жилые помещения; мультидипольная модель; линии электропередачи; распределительные устройства; токопроводы; transformation substation; external magnetic field; living spaces; multi-dipole model; methods of normalization